Spontaneous Intramuscular Hematomas in Patients with Severe COVID-19 (Case Report) - N. A. Lesteva; G. Yu. Rybakov; I. N. Danilov; A. A. Kovalev; A. N. Kondratyev (Общая реаниматология)
Aim of the study. To evaluate the risk factors for the occurrence of intramuscular hematomas in patients with severe coronavirus infection receiving anticoagulant therapy.Materials and methods. Intramuscular hematomas in five patients with severe COVID-19 disease are reported in the paper. The criteria for selecting patients for the study included respiratory distress requiring oxygen, radiographic signs of severe pneumonia, anticoagulant therapy using low molecular weight heparin (LMWH), and spontaneous intramuscular hematoma. Clinical manifestations, blood coagulation results, conservative and surgical management were analyzed.Results. Standard regimen anticoagulation therapy in patients with coronavirus infection requires vigilance because of a risk of development of hemorrhagic complications.Сonclusion. When assessing a patient with hematomas, an emphasis should be given to examination of patients and changes in hemoglobin and hematocrit levels. Best strategy of anticoagulant therapy for patients with coronavirus infection and high risk of VTE, as well as optimal laboratory monitoring during LMWH administration are yet to be explored.